Crosstalk between MSC-extracellular vesicles and Olea europaea leaf extract in encapsulated liposomal hydrogel: attenuation of neuroinflammation and brain neurotransmitter and memory impairment associated with obesity-induced high-fat diet - Ibrahim, Doaa; Pet, Ioan; Sherkawy, Hoda S.; Eldoumani, Haitham; Fathy, Ola M.; Elgamal, Aya; Gharib, Heba S. A.; Muhammed, Asmaa A.; Metwally, Aya Sh.; Ahmadi, Mirela; Puşcaşiu, Daniela; Abdel-Raheem, Sherief M.; et al. (Frontiers in Pharmacology, 2025)
Consumption of a high-fat diet (HFD) can trigger neuroinflammation, which may contribute to and increase the risk of neurodegenerative disease progression, ultimately leading to memory impairment. In the current study, the curative impact of a novel therapy combining Olea europaea leaf extract (OLE) encapsulated in a liposomal hydrogel (Lipo-OLE-Hydrogel) and mesenchymal stem cell-derived exosomes (MSC-Exo) was evaluated against HFD-induced brain dysfunction in a rat model. This assessment involved analyzing behavioral tasks, neurotransmitter levels, oxidative stress, neuroinflammation, endoplasmic reticulum-related markers, histopathological lesions, and immunostaining markers in brain tissues. The experimental groups were arranged for a 14-week study as follows: the first group received a control diet; the second group was fed an HFD; the third group was fed an HFD and treated with Lipo-OLE-Hydrogel; the fourth group was fed an HFD and treated with MSC-Exo; and the fifth group was fed an HFD and treated with both Lipo-OLE-Hydrogel and MSC-Exo. The findings of this study demonstrated that the neuroprotective effect of the combined Lipo-OLE-Hydrogel and MSC-Exo treatment was associated with a significant reduction in oxidative stress, as evidenced by the restoration of total antioxidant capacity and the marked decrease in oxidative biomarkers, including reactive oxygen species (ROS), H2O2, and malondialdehyde (MDA). The HFD-fed group exhibited greater glucose intolerance and increased body weight gain; however, these effects were significantly reversed in the group treated with the combination of Lipo-OLE-Hydrogel and MSC-Exo, even after long-term HFD induction. Impairments in behavioral tasks and memory were significantly improved in the group treated with the combined MSC-Exo and Lipo-OLE-Hydrogel therapy, with the MSC-Exo-alone group showing moderate improvement. The excessive inflammatory response and expression of endoplasmic reticulum stress-related genes were markedly attenuated following administration of Lipo-OLE-Hydrogel and MSC-Exo. This effect was mediated through the downregulation of pro-inflammatory and stress-related genes, including IL-6, COX-2, iNOS, TLR2, TLR4, NLRP3, CHOP, JNK, XBP1, and ATF6. The severity of the histopathological changes in the brain tissues, including the development of neoplastic epithelium and the invasion of some neoplastic masses, was significantly attenuated in the group treated with the combined Lipo-OLE-Hydrogel + MSC-Exo therapy. Immunohistochemical staining displayed that Bcl-2 protein expression was significantly restored to near normal levels, while TNF-α expression was significantly reduced in the group treated with the combined MSC-Exo and Lipo-OLE-Hydrogel therapy. Taken together, these findings highlight a novel and promising therapeutic approach that combines a natural protective agent (Lipo-OLE-Hydrogel) with regenerative medicine (MSC-Exo) to effectively combat the progression of HFD-induced neuroinflammation.